Competências na organização curricular da reforma do ensino médio - Casimiro Lopes, Alice (Boletim Técnico do Senac, 2001)
It analyses the conception of a competency-based curriculum of Brazilian middle-level education. This form of curriculum organization is understood as part of regulative discourse (Basil Bernstein) of this reform. It also argues that the competency-based curriculum is centered on social efficiency’s theories. As a regulative discourse, the competency-based curriculum and the subject-centered curriculum control school knowledge, especially by evaluation.